2017
DOI: 10.1002/jms.3909
|View full text |Cite
|
Sign up to set email alerts
|

First UHPLC-MS/MS method coupled with automated online SPE for quantification both of tacrolimus and everolimus in peripheral blood mononuclear cells and its application on samples from co-treated pediatric patients.

Abstract: Tacrolimus (TAC, FK-506) and everolimus (EVE, RAD001) are immunosuppressors used to treat pediatric patients undergoing liver transplantation. Their hematic TDM by liquid chromatography became standard practice. However, it does not always reflect concentrations at their active site. Our aim was to develop and validate a new method for the simultaneous TAC and EVE quantification into target cells: peripheral blood mononuclear cells (PBMCs). Peripheral blood mononuclear cells were collected using cell preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…One can raise the hypothesis that it might be due to the normalization of TAC intra-PBMC concentration in quantity per number of cells instead of volumetric unit. Indeed, as suggested by Pensi et al, it would be more accurate to normalize intracellular concentration by the mean cell volume of each patient [7,36]. Unfortunately, measurement of cells volume was not available on the instrument use in our study and we could not check whether the underestimated concentrations were due to extreme values in PBMC volumes in these individuals.…”
Section: Discussionmentioning
confidence: 85%
“…One can raise the hypothesis that it might be due to the normalization of TAC intra-PBMC concentration in quantity per number of cells instead of volumetric unit. Indeed, as suggested by Pensi et al, it would be more accurate to normalize intracellular concentration by the mean cell volume of each patient [7,36]. Unfortunately, measurement of cells volume was not available on the instrument use in our study and we could not check whether the underestimated concentrations were due to extreme values in PBMC volumes in these individuals.…”
Section: Discussionmentioning
confidence: 85%
“…In liver transplant recipients, [Tac] cells significantly correlated with both the development and the severity of rejection 8 . Moreover, previous studies reported poor to moderate correlations between [Tac] cells and [Tac] blood , indicating that [Tac] blood does not always reflect the concentration at the target site 8,11,13–17 …”
Section: Introductionmentioning
confidence: 98%
“…8 Moreover, previous studies reported poor to moderate correlations between [Tac] cells and [Tac]blood , indicating that [Tac] blood does not always reflect the concentration at the target site. 8,11,[13][14][15][16][17] This poor correlation may reflect the activity of the efflux transporter protein ABCB1 in mononuclear cell membranes. Differences in ABCB1 activity may result in differences in intralymphocytic tacrolimus accumulation and tacrolimus pharmacodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…30 Also, as these samples contain high and variable amounts of cells and phospholipids that may affect the analysis, evaluation of the matrix effect is critical. 31,32 In contrast to the above-described alternative sample matrices, CSF requires highly invasive sampling from lumbar puncture. For several drugs, similar to PBMCs, the concentration in CSF directly reflects the concentration at the target site.…”
Section: Alternative Matricesmentioning
confidence: 99%
“…However, intracellular TDM is not (yet) routinely performed, due to a lack of standardised collection/isolation and cell count procedures for the processing of PBMCs, both of which influence the accuracy of the quantitative measurements 30 . Also, as these samples contain high and variable amounts of cells and phospholipids that may affect the analysis, evaluation of the matrix effect is critical 31,32 …”
Section: Sampling Strategiesmentioning
confidence: 99%